Use of computer stimulating programs in patients with post-stroke cognitive impairment - S. V. Prokopenko; T. V. Dyadyuk; E. Yu. Mozheyko; A. F. Bezdenezhnykh; T. D. Koryagina; T. S. Anay-Ool (Неврология, нейропсихиатрия, психосоматика)
Objective: to evaluate the efficiency of using computer stimulation programs (CSPs) for acute ischemic stroke (IS) in patients with cognitive impairment (CI).Patients and methods. 81 patients aged 40 to 79 years with post-stroke CI (PSCI) were examined and randomized into two groups. A study group consisted of 45 people, including 31 and 14 patients with predementia CI and mild dementia, respectively; their median age was 61 [55; 68] years. A comparison group included 36 patients, including 21 and 15 patients with predementia CI and mild dementia; their median age was 64 [57; 70] years. In addition to standard stroke therapy, the study group received a ten-day correction cycle for CI, by using CSPs.Cognitive functions (CF) were evaluated before and after classes, by applying a short mental status questionnaire (SMSQ), a battery of frontal lobe dysfunction tests (BFLDT), a clock drawing test, and a speech activity test.Results. After 10 days of therapy (at 18–20 days of IS), the patients were observed to have statistically significant improvements of cognitive functions in all major neuropsychological scales: SMSQ, BFLDT, a clock drawing test, and a speech activity test (p>0.05).Assessing the total indicators of SMSQ subtests in both groups showed that the study group achieved statistically significant differences in memory, time and place orientation, and concentration. In the study group, the total values of BFTLD subtests were also statistically better in indicators, such as speech fluency (by 33.0%), dynamic praxis (by 23.3%), a simple choice reaction (by 30.0%), and a complicated choice reaction (by 26.7%). At the same time, not only trained functions (attention, memory), but also other cognitive indicators improved. Re-examination demonstrated that the achieved results persisted 6-8 months later.Conclusion. CSPs are a promising area of neurorehabilitation. The method is effective, easy-to-use; the patients can do lessons at hospital and at home after discharge in the presence of relatives or themselves. Further investigations will be able to evaluate the effectiveness of CSPs in patients with PSCI in the later periods of IS.